Human skeletal remains - White, Teresa A., author.
1 online resource (120 pages)
Keywords: Human Skeletal Remains is a step-by-step field guide to teach proper recovery techniques when a forensic anthropologist is unavailable for immediate scene responses.In the absence of a forensic anthropologist, the investigator assumes the responsibility of ensuring the complete and accurate recovery of skeletal materials from scenes. This could be problematic if the investigator has not had specialized training in human remains recoveries. To help investigators carry out this task, the authors developed this guide using 328 full-color demonstrative photos with easy-to-follow instructions on how to identify and recover human skeletal remains using scientifically defensible methods. It is an excellent resource for law enforcement, medicolegal death investigators, CSIs, anthropologists, medical examiners, coroners, evidence recovery technicians, students, and other forensic professionals.Features Side-by-side photographic comparisons of adult and juvenile human remains with nonhuman bones Start to finish demonstration of proper recovery techniques involving scenes with surface scattered and buried human remains Preservation considerations with respect to cultural sensitivity and ethical practices Human Skeletal Remains is an illustrative tool designed to accompany you on scene. Use it to identify the bones you locate, then follow the instructions to recover them. Get it dirty!